An assessment of workplace skills acquired by students of vocational and technical education institutions. - Bakar, Ab Rahim; Mohamed, Shamsiah; Hamzah, Ramlah (Canadian Center of Science and Education, 2013)
This study was performed to identify the employability skills of technical students from the Industrial Training Institutes (ITI) and Indigenous People’s Trust Council (MARA) Skills Training Institutes (IKM) in Malaysia. The study sample consisted of 850 final year trainees of IKM and ITI. The sample was chosen by a random sampling procedure from a population of 2520 students from both institutions. Trainees’ employability skills were measured using a 40 item questionnaire adapted from the Secretary’s Commission on Achieving Necessary Skills (SCANS) report. In general, the majority of the trainees possessed a moderate level of employability skills (Mean= 3.88, S.D= .49). Their basic skills were at the moderate level (Mean= 3.83, S.D= .9); thinking skills (Mean= 3.73, S.D= .56); source skills (Mean= 3.83, S.D= .57); informational (Mean= 3.61, S.D= .76); interpersonal (Mean= 3.92, S.D= .57); technical and system skills (Mean= 3.81, S.D= .67); and self-qualities (Mean= 4.14, S.D= .55). There were no significant differences of employability skills between trainees from IKM and ITI in term of gender, work experience, and between courses.